FACTORS SHAPING A CRIMINOGENIC SITUATION AND THEIR CLASSIFICATION (IN THE CASE OF FERGANA REGION) (Scientific journal of the Fergana State University, 2026)
The article provides a deep analysis of the factors influencing the crime situation in the Fergana region. Based on international and domestic scientific sources, a classification of factors influencing crime has been developed, with the allocation of their territorial, socio-economic, spiritual, organizational and psychological categories. The dynamics and characteristics of crime in the Fergana region have been studied in comparison with other CIS countries and foreign experience. As a result, a comparative table of the system classification of criminogenic factors has been presented using the example of the Fergana region and foreign regions, factors causing crime and their differences have been identified. The results of the article serve to develop measures to prevent crime on a scientific basis.